2017
DOI: 10.1177/1535370217718808
|View full text |Cite
|
Sign up to set email alerts
|

Protective regulation of the ACE2/ACE gene expression by estrogen in human atrial tissue from elderly men

Abstract: The present study demonstrates that estrogen affects the human atrial myocardium and mediates protective actions through estrogen receptors-(ER) dependent signaling. Estrogen substantially modulates the local RAS via downregulation of ACE and simultaneous upregulation of ACE2, AT2R and MAS expression levels. This is indicative of a shift of the classical RAS/ACE axis to the alternative, protective RAS/ACE2 axis. In support of this view, estrogen attenuated the expression of RAS-associated downstream effectors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(193 citation statements)
references
References 62 publications
4
183
0
1
Order By: Relevance
“…4 The circulating levels of ACE2 in the low SYNTAX score, intermediate SYNTAX score and high SYNTAX score groups the ACE2-Ang-(1-7)-MAS axis does exist, which may be mediated, in part, by sex hormones. For example, estrogen has been demonstrated to associate with nonclassical RAS components including ACE2, Ang-(1-7) and MasR activity [32][33][34]. In addition, gender differences in the presentation, prevalence and clinical outcomes of CHD are known to exist [35], thus we performed sex-specific analyses subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…4 The circulating levels of ACE2 in the low SYNTAX score, intermediate SYNTAX score and high SYNTAX score groups the ACE2-Ang-(1-7)-MAS axis does exist, which may be mediated, in part, by sex hormones. For example, estrogen has been demonstrated to associate with nonclassical RAS components including ACE2, Ang-(1-7) and MasR activity [32][33][34]. In addition, gender differences in the presentation, prevalence and clinical outcomes of CHD are known to exist [35], thus we performed sex-specific analyses subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…This has raised a theoretical concern that by increasing ACE-2 expression, ACEIs and ARBs could facilitate the entry of virus into the host cell and increase the chances of infection or its severity [17]. Also, there is increased ACE-2 expression in elderly [37]. To what extent this predisposes the elderly to infection with SARSCoV2 is not known.…”
Section: Effects Of Ace Inhibitors and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…The deprivation of estrogen in post-menopause causes a loss of cardiovascular protection in women due to the possible shift from the ACE2/RAS axis to the ACE/RAS pathways [55]. Shoemaker et al showed that adipocyte-derived ACE2 contributes to sex differences in obesity-hypertension through the regulation of the balance between Ang-(1-7) and Ang II, a benefit that is lost with estrogen deprivation in post-menopause [56].…”
Section: Can Ras Targeting Be An Important Option For Covid-19?mentioning
confidence: 99%